Chapter 6 — Urban Design for a Wind Resistant Urban Forest - Edward F. Gilman; Traci Partin (EDIS)
ENH1056, an 8-page full-color fact sheet by Edward F. Gilman and Traci Partin, is part of the Urban Forest Hurricane Recovery Program series. It describes how to adjust existing design situations where roots are in conflict with the landscape, how to design new situations where space is limited, sustainable parking lot design, and tree selection. Published by the UF Department of Environmental Horticulture, September 2007.